Transforming Education Outcomes in Africa: Learning from Togo (International Journal of Multidisciplinary Perspectives in Higher Education, 2019)
Book Review of Transforming Education Outcomes in Africa: Learning from TogoEdited by Johannes Hoogeveen & Mariacristina Rossi